2017
DOI: 10.3390/ijms18091869
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Distribution of RAPTA-T in Non-Invasive and Invasive Breast Cancer Cells Correlates with Its Anti-Invasive and Anti-Metastatic Effects

Abstract: Nanoscale secondary ion mass spectrometry (NanoSIMS) combined with transmission electron microscopy (TEM) can be a powerful approach to visualize the exact distribution of drugs at the sub-cellular level. In this work, we exploit this approach to identify the distribution and localisation of the organometallic ruthenium(II)-arene drug Ru(η6-C6H5Me)(pta)Cl2, termed RAPTA-T, in MDA-MB-231 and MCF-7 human breast cancer cells. These cell lines have been chosen because the former cell lines are highly invasive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…Recent studies have indicated that the nucleolus is multifunctional, with roles in gene stability and silencing, cell‐cycle regulation, stress, and immune response (Boisvert, van Koningsbruggen, Navascues, & Lamond, ; Grummt, ). For example, recent NanoSIMS analyses have shown that cancer drugs, which influence these sorts of activities in the cell, showed strong stable‐isotope labelling in the nucleolus (Lee et al, ; Lee et al, ). Further, all processes of the above‐mentioned functions of the nucleolus are ones that are influenced by interactions with microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the nucleolus is multifunctional, with roles in gene stability and silencing, cell‐cycle regulation, stress, and immune response (Boisvert, van Koningsbruggen, Navascues, & Lamond, ; Grummt, ). For example, recent NanoSIMS analyses have shown that cancer drugs, which influence these sorts of activities in the cell, showed strong stable‐isotope labelling in the nucleolus (Lee et al, ; Lee et al, ). Further, all processes of the above‐mentioned functions of the nucleolus are ones that are influenced by interactions with microbes.…”
Section: Discussionmentioning
confidence: 99%
“…[104,105] Interestingly, all three compounds appear to have the capacity to inhibit angiogenesis. [40,52,70] Nevertheless, it has been shown that the anti-angiogenic efficacy of NAMI-A is limited to the inhibition of endothelial cell (human progenitor endothelial cells HPEC-CB.2) motility and migration, but does not affect pseudovessel formation of mammary epithelial cells (HSkMEC) under normoxic or hypoxic conditions. [40] Remarkably, rutheniumbased complexes share the characteristic to block blood vessel formation and cellular migration, which decreases the nutrition supply toward the tumor site and therefore adds efficacy for sufficient cancer treatment.…”
Section: Rapta-c Versus Kp1019/(n)kp1339 and Nami-amentioning
confidence: 99%
“…Receptor‐dependent uptake of RAPTA‐C therefore relates to increased distribution and enhanced accumulation in cancer cells with upregulated receptor expression, whereby healthy cells remain less affected . Moreover, RAPTA‐C exhibits no discernable cytotoxic effects on healthy cells and severe side effects have not been observed in in vivo models ( Table ) …”
Section: Rapta‐c In Comparison To Clinically Applied Metal‐based Prodmentioning
confidence: 99%
“…Like well‐established Pt II anticancer drugs (cisplatin, carboplatin and oxaliplatin), these complexes contain relatively labile chlorido ligands that can be exchanged for donor groups of proteins and nucleic acids . The greater affinity for Ru‐chlorido ligand substitution in biological media relative to those of Pt II complexes leads to predominant binding of Ru II or Ru III antimetastatic drugs to biomolecules in the extracellular space, or at the cell surface, rather than to intracellular targets . The resultant disruption in communication between the cell surface and extracellular matrix is thought to be the main cause of antimetastatic activities of NAMI‐A, RAPTA‐T and related Ru complexes .…”
Section: Introductionmentioning
confidence: 99%
“…The greater affinity for Ru‐chlorido ligand substitution in biological media relative to those of Pt II complexes leads to predominant binding of Ru II or Ru III antimetastatic drugs to biomolecules in the extracellular space, or at the cell surface, rather than to intracellular targets . The resultant disruption in communication between the cell surface and extracellular matrix is thought to be the main cause of antimetastatic activities of NAMI‐A, RAPTA‐T and related Ru complexes . However, the high reactivity of NAMI‐A in biological media has also led to Ru binding to nontarget tissues, which has caused excessive side effects that led to withdrawal of the drug from phase II clinical trials .…”
Section: Introductionmentioning
confidence: 99%